2013
DOI: 10.5433/1679-0359.2013v34n1p83
|View full text |Cite
|
Sign up to set email alerts
|

Produtividade e acúmulo de nutrientes em plantas de jambu, sob adubação orgânica e mineral

Abstract: ResumoA produção orgânica é um sistema que permite alcançar bons níveis de produtividade, evitando ao mesmo tempo os riscos de contaminação química do agricultor, dos consumidores e do meio ambiente. Pelo fato da planta de jambu ser bastante utilizada como medicamento alternativo e por indústrias de cosméticos, vem aumentando o interesse pelo seu cultivo. Assim, o objetivo desse trabalho foi analisar a biomassa, acúmulo de nutrientes, a produtividade e determinar o resíduo de agrotóxico em plantas de jambu qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
2
17

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 4 publications
2
18
2
17
Order By: Relevance
“…2 more accumulation of biomass (Milhomens et al, 2015;Rós et al, 2016). To jambu, Borges et al (2013) and Rodrigues et al (2014) observed significant answers at the production, in function of the increase of nitrogen fertilization in soil. In this context, the linear increase of biomass production suggests that the specie can still respond to higher concentrations of this nutrient in nutritive solution, which indicates high responsiveness from plant to element.…”
Section: Results From Researches Have Revealed That the Increase Of Nmentioning
confidence: 99%
See 2 more Smart Citations
“…2 more accumulation of biomass (Milhomens et al, 2015;Rós et al, 2016). To jambu, Borges et al (2013) and Rodrigues et al (2014) observed significant answers at the production, in function of the increase of nitrogen fertilization in soil. In this context, the linear increase of biomass production suggests that the specie can still respond to higher concentrations of this nutrient in nutritive solution, which indicates high responsiveness from plant to element.…”
Section: Results From Researches Have Revealed That the Increase Of Nmentioning
confidence: 99%
“…The relation of nitrogen fertilization and the N accumulation in jambu plants was demonstrated for Borges et al (2013), where it was observed increasing of N accumulation when it was elevated the doses of urea in soil. In vegetables, N supports the vegetative development, resulting in leaf area expansion, in addition of influence the productive potential (Filgueira, 2013).…”
Section: Journal Of Agricultural Studiesmentioning
confidence: 96%
See 1 more Smart Citation
“…É uma hortaliça rica em elementos nutritivos, com presença de vitaminas B 1 , B 2 , niacina, vitamina C, vitamina A e cálcio (BORGES et al, 2012). As inflorescências são pequenas e amareladas, dispostas em capítulos.…”
Section: Informações E Importância Da Espécieunclassified
“…O processo de patenteamento para novos produtos no exterior e uso na gastronomia nacional e internacional estão transformando o jambu em uma hortaliça promissora. (BORGES, 2012).…”
Section: Informações E Importância Da Espécieunclassified